Follow the child: the effect of an unconditional cash transfer on adolescent human capital and mental health - Eyal, Katherine (School of Economics, 2017)
In company with many other developing countries in the 1990s, South Africa introduced an unconditional cash transfer program for children, which had more than eleven million beneficiaries in 2014. The evaluation of similar cash transfer programs is a widely researched space, however much of the literature focuses on younger children, and outcomes which are both short term, and tangible, such as school enrolment or physical health. Limited research has been conducted on the impact of cash transfers on adolescents and their caregivers, and in particular there is a scarcity of studies on the impact of transfers on the mental health of recipients. This thesis exploits exogenous variation in grant receipt to estimate the current and cumulative grant impacts on the educational and mental health outcomes of teenagers, and the channels through which these effects may take place. The grant is found to have large positive effects on teen enrolment, yet no gains in human capital achievement are seen. The mental health of adolescents is also an under studied area, both domestically and internationally, with few, if any studies performed on the impact of cash transfers on the intergenerational transmission of depression (the single largest determinant of adolescent mental health). This thesis finds that the child support grant largely reduces the impact of a depressed parent on teen mental health, and in particular the grant minimises the considerable negative effect of depressed fathers on teens. There is a literature which suggests that these improvements in teen welfare may stem from improved female bargaining power, which directs more resources to child specific needs, or improved maternal mental health, which improves the parenting and environment experienced by the teen, encouraging both educational achievement and better mental health. Despite this, investigation reveals that the grant has no positive effect on maternal mental health, and if an effect exists for maternal bargaining power, it is very small. This is likely to be due to the relatively modest size of the transfer. This is unfortunate, as this work finds that maternal mental illness has a significant negative impact on teen human capital attainment.